Silsesquioxane resin coating and preparation method thereof

By introducing cage polysilsesquioxane into trapezoidal polysesquioxane resin to form a crosslinking network, the solubility and aggregation problems of cage polysesquioxane are solved, and high hardness and flexibility are achieved. Transparent flexible coating meets the industry's demand for high hardness and transparency.

CN119307179APending Publication Date: 2025-01-14BEIJING UNIV OF CHEM TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411611801.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The problem of limited solubility and easy aggregation at high concentrations of cage polysilsesquioxanes is difficult to widely use in industrial applications in the prior art. At the same time, the hardness and transparency of the traditional trapezoid polysesquioxane coating are insufficient, which is difficult to meet. The industry requires high hardness and flexibility.

Method used

By introducing cage polysilsesquioxane into trapezoidal polysesquioxane resin, a dense crosslinking network is formed, and a high-hard transparent flexible wear-resistant coating is prepared through ultraviolet curing technology to optimize cage polysesquioxane The ratio and process flow of semisiloxane.

Benefits of technology

The coating performance is achieved with high hardness, excellent flexibility and excellent transparency, with a radius of bending curvature as low as 0.35mm, a light transmittance of up to 99.6%, a pencil hardness greater than 9H, and a nano-indentation hardness and modulus reaching the leading level, which proves that The coating has high hardness and bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307179A_ABST
    Figure CN119307179A_ABST
Patent Text Reader

Abstract

The invention discloses a silsesquioxane resin coating and a preparation method thereof, and belongs to the field of advanced coating preparation. The polyhedral oligomeric silsesquioxane is introduced into the trapezoidal polysilsesquioxane resin as a modifier through chemical bonding to form a compact cross-linked network, and the mechanical property of the coating is remarkably improved by virtue of the rigid structure of the polyhedral oligomeric silsesquioxane. In addition, the coating can be rapidly photocured through irradiation of an ultraviolet lamp to form a high-hardness transparent flexible wear-resistant coating, and has good process applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced coating preparation, and more specifically, relates to a transparent, flexible, wear-resistant coating with high hardness prepared by using cage-type polysilsesquioxane reinforced trapezoidal polysilsesquioxane and a preparation method thereof. Background Art

[0002] Hard, wear-resistant coating materials with high transparency are widely used in various industries, including electronics, optics, automobiles, and construction. In recent years, flexible hard coatings with glass-like wear resistance as protective windows for flexible displays have gradually become the focus of industry attention due to the emergence of the foldable smartphone industry. In addition, these coatings are increasingly used in the field of plastic windows for automobiles and buildings due to their advantages such as light weight, convenience, and safety. With the development of science and technology and the progress of society, many application fields have higher and higher requirements for the hardness and wear resistance of protective coatings. However, there are few materials that are both wear-resistant and bendable, and films made using only inorganic materials are hard and heat-resistant. But their lack of flexibility and plasticity can lead to cracking, hindering the development of functional films. In contrast, although organic coatings generally have excellent flexibility, their hardness and scratch resistance are often insufficient. Therefore, it is highly desirable to develop a coating material that can provide high flexibility and wear resistance to the substrate while maintaining excellent hardness and optical transparency.

[0003] Cage-type polysilsesquioxanes are silica-based compounds with polymer nanostructures. Due to their unique chemical and physical properties, they have become promising materials for the development of advanced coatings. The internal rigid siloxane cage provides a stable framework for resisting thermal, chemical and mechanical stresses, while the external organic groups can be precisely functionalized using known chemical techniques. Therefore, cage-type polysilsesquioxanes are used to prepare protective coatings with high hardness and excellent flexibility. This coating combines high hardness and excellent flexibility, while showing excellent mechanical properties - hardness comparable to glass, plastic-like flexibility, and significant crack resistance. Polysilsesquioxane is easier to control than silica, and due to its organic functional groups, it can be further modified to improve the comprehensive performance of the material. In addition, it is compatible with organic polymer matrices and can be used with a variety of organic and inorganic fillers. It is one of the ideal choices for making high-transparency, flexible, hard and wear-resistant coating materials. Chinese patent 202210179395.0 discloses a highly transparent, flexible, scratch-resistant coating material modified with silsesquioxane monomers. The resulting coating has a light transmittance of up to 96%, a surface pencil hardness of up to 9H, a nanoindentation hardness and modulus ratio H / E of up to 0.33, and a bending radius of curvature as low as 0.25mm. At the same time, Chinese patent 202310036876.0 also discloses a cage-type polysilsesquioxane hybrid epoxy anticorrosive coating and its coating. Through a thiol click reaction, vinyl POSS is grafted into the epoxy resin system, giving the coating excellent mechanical properties and anticorrosion properties.

[0004] In summary, in order to meet the industry's urgent demand for advanced coating materials, we proposed to modify epoxy ladder silsesquioxane resin with cage-type polysilsesquioxane to prepare a high-hardness, transparent, flexible, and wear-resistant coating. Summary of the invention

[0005] The present invention found that although the application of cage-type polysilsesquioxane as a modifier in the field of coating resins has been widely explored, its limited solubility and easy aggregation at high concentrations limit its widespread use in industrial applications. In contrast, trapezoidal polysilsesquioxane can not only form a uniform phase and maintain excellent transparency, but also has excellent hardness comparable to that of cage-type polysilsesquioxane. In addition, by constructing a cross-linked network with organic groups on an inorganic core, trapezoidal polysilsesquioxane can help develop coatings that are both optically transparent and have high hardness. It is worth mentioning that the traditional method of producing trapezoidal polysilsesquioxane coatings often introduces organic functional groups such as methacrylate or epoxy, so that the coating can be cured by ultraviolet light. This feature brings great convenience to the processing and application of the coating.

[0006] The present invention provides a transparent, flexible, and wear-resistant coating with high hardness prepared by modifying trapezoidal polysilsesquioxane with cage-type polysilsesquioxane, and a preparation method thereof. The rigid cage structure of the cage-type polysilsesquioxane is introduced into the trapezoidal polysilsesquioxane through a chemical reaction, so as to further improve the mechanical properties of the coating. The selection and proportion of the cage-type polysilsesquioxane have certain novelty and innovation. In order to explore the influence of the cage-type polysilsesquioxane on the comprehensive performance of the trapezoidal polysilsesquioxane resin coating, we prepared a series of siloxane resin coatings with different proportions, and the coating preparation process also has certain practicality. The silsesquioxane resin coating prepared by our method exhibits excellent performance: the bending radius can be as low as 0.35 mm, showing excellent flexibility; the light transmittance is as high as 99.6%, ensuring the transparency of the coating; the pencil hardness is greater than 9H, the nanoindentation hardness H can reach up to 1.56GPa, and the modulus reaches 13.90GPa, all of which show the high hardness and high strength of the coating. In addition, the H / E ratio is 0.11 and the elastic recovery rate (We) is 83.10, which further confirms the bending resistance and wear resistance of the coating. In the current research field of protective coatings with high hardness and excellent flexibility, the coating we prepared has reached a leading level in hardness. This polysilsesquioxane resin coating not only has certain novelty, but also shows great potential and advantages in practical applications, providing a new direction for the development of transparent flexible wear-resistant coatings.

[0007] The first problem solved by the present invention is to introduce cage-type polysilsesquioxane as a modifier into ladder-type polysilsesquioxane.

[0008] The second problem solved by the present invention is the preparation of a transparent flexible scratch-resistant coating with high hardness.

[0009] In order to solve the above invention problem, the following technical solution is adopted:

[0010] A method for reinforcing a trapezoidal polysilsesquioxane resin by using a cage-type polysilsesquioxane is used to prepare a transparent, flexible, wear-resistant coating with high hardness, and the implementation steps are as follows:

[0011] (1) Cage-type polysilsesquioxane and ladder-type polysilsesquioxane were prepared by hydrolysis-condensation reaction;

[0012] (2) The cage-type polysilsesquioxane prepared in (1) is added as a modifier to the trapezoidal polysilsesquioxane to form a dense cross-linked network through a chemical reaction, which can be quickly photocured by ultraviolet light to form a transparent, flexible, and wear-resistant coating with high hardness.

[0013] Preferably, the cage-type polysilsesquioxane in step (1) forms a cross-linked network by chemically reacting with the ladder-type polysilsesquioxane.

[0014] Preferably, the general chemical formula of the cage-type polysilsesquioxane is Si x O y R x , wherein x is 6, 7, 8, 10 or 12, y=1.5x, and R is at least one of an epoxy group, an amino group, a carbonyl group, an ester group, a hydroxyl group, a mercapto group, a halogen atom, an ether group and an olefin.

[0015] Preferably, the cage-type polysilsesquioxane is selected from at least one of the substances described in the following structural formulas:

[0016] Preferably, the ladder-shaped polysilsesquioxane chemical formula of step (1) is (SiRO 1.5 ) n , wherein R is at least one of an epoxy group, an amino group, a carbonyl group, an ester group, a hydroxyl group, a mercapto group, a halogen atom, an ether group and an olefin.

[0017] Preferably, the ladder-shaped polysilsesquioxane structural formula is as follows:

[0018] A method for reinforcing a trapezoidal polysilsesquioxane resin by using a cage-type polysilsesquioxane is provided for preparing a transparent, flexible, wear-resistant coating with high hardness. The preparation process of the cage-type polysilsesquioxane is based on cage-type epoxy polysilsesquioxane as an example:

[0019] First add a certain amount of catalyst and deionized water to a three-necked flask, then place it in a hot oil bath for stirring, and then add the solution of the silane raw material to the three-necked flask. After the addition is completed, start heating, control the temperature at 30°C, and continue stirring and heating at this temperature for hydrolysis. Then transfer the obtained hydrolysis system to remove the solvent to obtain a colorless, transparent, viscous liquid. Dissolve the above substances fully with toluene, transfer to a three-necked flask, place it in an oil bath, and continue to react the system under reflux for a period of time to obtain a light yellow transparent liquid, and then remove the toluene through post-treatment to obtain a translucent viscous liquid.

[0020] A method for reinforcing a trapezoidal polysilsesquioxane resin by using a cage-type polysilsesquioxane is used to prepare a transparent, flexible, wear-resistant coating with high hardness. The preparation process of the trapezoidal polysilsesquioxane is as follows:

[0021] Deionized water, tetrahydrofuran solvent and alkaline catalyst are added to a three-necked flask and stirred until the solution is clear and transparent; then siloxane monomer is added dropwise and reacted at room temperature for 1 to 3 days; after the reaction is completed, the obtained reaction solution is dissolved in an organic solvent, extracted with deionized water for multiple times until the solution is neutral, and after drying, the solvent is removed by rotary evaporation to obtain trapezoidal polysilsesquioxane.

[0022] Preferably, the organic solvent is tetrahydrofuran, methanol, ethanol, ethyl acetate, butyl acetate, dichloromethane, benzene, toluene, xylene, cyclohexane, acetone, chloroform, ether or dimethylformamide, and at least one of tetrahydrofuran, methanol, ethanol, ethyl acetate, butyl acetate, dichloromethane, benzene, toluene, xylene, cyclohexane, acetone, chloroform, ether or dimethylformamide that has been purified, and dichloromethane is more preferred.

[0023] A method for reinforcing a trapezoidal polysilsesquioxane resin by using a cage-type polysilsesquioxane is used to prepare a transparent, flexible, and wear-resistant coating with high hardness. The coating preparation process is as follows:

[0024] A certain mass of trapezoidal polysilsesquioxane and cage polysilsesquioxane is weighed and dissolved in an organic solvent, and then a photoinitiator is added and ultrasonically dissolved until clear and transparent; the sample is evenly coated on a substrate, and then the substrate coated with the sample is placed in a light-proof oven to dry to completely remove the solvent; finally, it is cured by ultraviolet light, and a high-hardness, flexible, and wear-resistant coating can be obtained after curing.

[0025] Preferably, the organic solvent is tetrahydrofuran, methanol, ethanol, ethyl acetate, butyl acetate, dichloromethane, benzene, toluene, xylene, cyclohexane, acetone, chloroform, ether or dimethylformamide, and at least one of tetrahydrofuran, methanol, ethanol, ethyl acetate, butyl acetate, dichloromethane, benzene, toluene, xylene, cyclohexane, acetone, chloroform, ether or dimethylformamide that has been purified, and dichloromethane is more preferred.

[0026] Preferably, the photoinitiator is at least one of a free radical photoinitiator or a cationic photoinitiator.

[0027] Preferably, the free radical photoinitiator is selected from a cleavage photoinitiator or a hydrogen abstraction photoinitiator, the cleavage photoinitiator is further preferably selected from at least one of benzoin and its derivatives, benzil and its derivatives, acylphosphine oxides or α-hydroxyketones and their derivatives, and the hydrogen abstraction photoinitiator is further preferably selected from at least one of benzophenone or heterocyclic aromatic ketone compounds;

[0028] Preferably, the cationic photoinitiator is selected from at least one of aryl diazonium salts, diaryl iodonium salts, triaryl sulfonium salts, alkyl sulfonium salts, iron arene salts, sulfonyloxy ketones, triaryl siloxane ethers or mixed triaryl sulfonium hexafluoroantimonate salts.

[0029] Preferably, the weight proportion of cage-type polysilsesquioxane in the polysilsesquioxane composition is 5-50%. It is found through experiments that when an excessive amount of cage-type polysilsesquioxane is added, the hardness of the silsesquioxane resin coating decreases. The reason may be that the free volume of the cage-type polysilsesquioxane is too large, and excessive introduction will affect the effective cross-linking of the epoxy groups in the system, reduce the cross-linking density, and thus lead to a decrease in the hardness of the coating. Therefore, it is further preferably 5-20%, and most preferably 10%;

[0030] Preferably, the material of the substrate includes at least one of polyethylene terephthalate, polyimide, polycarbonate, polymethyl methacrylate, cellulose polymer, glass fiber reinforced composite material, glass, metal, polyethylene terephthalate, polyimide, polycarbonate, polymethyl methacrylate, glass or metal with organic or inorganic surface treatment;

[0031] Preferably, the coating composition is uniformly coated on the surface of the substrate by any of drop coating, spin coating, rod coating, blade coating and spray coating;

[0032] Preferably, the wavelength of the ultraviolet lamp is 200-400nm;

[0033] Preferably, the UV lamp curing irradiation time is 10 to 30 minutes. Through real-time infrared monitoring of the conversion rate and polymerization rate of the epoxy group during the reaction, it is found that the epoxy conversion rate can reach more than 60% after 15 minutes of UV light irradiation. The irradiation time is extended to ensure sufficient reaction of the epoxy group. Therefore, 30 minutes is further preferred.

[0034] A method for reinforcing a trapezoidal polysilsesquioxane resin by using a cage-type polysilsesquioxane is used to prepare a transparent, flexible, wear-resistant coating with high hardness, wherein the coating-coated substrate needs to be cleaned with a solvent. Preferably, the solvent is at least one of deionized water, acetone, isopropanol, ethanol, toluene, and butyl acetate. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and are not to be construed as limiting the scope of protection of the present invention. Those skilled in the art may make some non-essential improvements and adjustments to the present invention based on the above-mentioned contents of the present invention.

[0037] Example 1

[0038] Add 1g of tetramethylammonium hydroxide and 20g of deionized water into a three-necked flask, and then put it into an oil bath for stirring; weigh 100g of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane and add it dropwise into the three-necked flask, and after the addition is completed, heat the reaction system to 30°C and stir for 4h; after the reaction is completed, spin dry the solvent, add 400ml of toluene to fully dissolve it, transfer it to a three-necked flask and continue heating and reflux for 4h; after the reaction is completed, remove the solvent to obtain cage-type 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane.

[0039] Add 40g of water and 12g of tetrahydrofuran solvent into a three-necked flask, then add 0.1g of potassium carbonate as a catalyst, and stir until the solution is clear and transparent; then add 98.552g of 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane dropwise, and react at room temperature for 72h; after the reaction is completed, dissolve the resulting reaction solution in 150ml of dichloromethane, and extract with deionized water several times until the solution is neutral; finally, remove the excess solvent to obtain trapezoidal 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane.

[0040] Take 1.9g of the trapezoidal 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane prepared above and 0.1g of the cage-type 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane, add 18g of tetrahydrofuran solvent to completely dissolve them, then add 0.01g of the cationic photoinitiator triarylsulfonium hexafluoroantimonate mixture and ultrasonicate until the solution is clear and transparent; then use a computerized coating machine to scrape the solution on the glass slide substrate and the polyimide substrate respectively. After coating, put it in a forced air drying oven and dry it at 65°C for 30 minutes. After the solvent is completely volatilized, cure it for 30 minutes under 365nm ultraviolet light and nitrogen atmosphere.

[0041] Example 2

[0042] Take 1.8g of the trapezoidal 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane and 0.2g of the cage-type 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane prepared in Example 1, add 18g of tetrahydrofuran solvent to completely dissolve them, and then add 0.01g of the cationic photoinitiator triarylsulfonium hexafluoroantimonate mixture and ultrasonicate until the solution is clear and transparent; then use a computerized coating machine to scrape the solution on the glass slide substrate and the polyimide substrate respectively. After coating, put it in a forced air drying oven and dry it at 65°C for 30 minutes. After the solvent is completely volatilized, cure it for 30 minutes under 365nm ultraviolet light and nitrogen atmosphere.

[0043] Example 3

[0044] Take 1.6g of the trapezoidal 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane and 0.4g of the cage-type 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane prepared in Example 1, add 18g of tetrahydrofuran solvent to completely dissolve them, and then add 0.01g of the cationic photoinitiator triarylsulfonium hexafluoroantimonate mixture and ultrasonicate until the solution is clear and transparent; then use a computerized coating machine to scrape the solution onto a glass slide substrate and a polyimide substrate, respectively. After coating, place it in a forced air drying oven and dry it at 65°C for 30 minutes. After the solvent is completely volatilized, cure it for 30 minutes under 365nm ultraviolet light and nitrogen atmosphere.

[0045] Comparative Example 4

[0046] Take 2g of the trapezoidal 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane prepared in Example 1 above, add 18g of tetrahydrofuran solvent to completely dissolve it, then add 0.01g of cationic photoinitiator triarylsulfonium hexafluoroantimonate mixture and ultrasonicate until the solution is clear and transparent; then use a computerized coating machine to scrape the solution on the glass slide substrate and the polyimide substrate respectively. After coating, put it into a forced air drying oven and dry it at 65°C for 30min. After the solvent is completely volatilized, cure it for 30min under 365nm ultraviolet light and nitrogen atmosphere.

[0047] Comparative Example 5

[0048] Take 2g of the cage-type 2-(3,4-epoxycyclohexane)ethyl polysilsesquioxane prepared in Example 1 above, add 18g of tetrahydrofuran solvent to completely dissolve it, then add 0.01g of cationic photoinitiator triarylsulfonium hexafluoroantimonate mixture and ultrasonicate until the solution is clear and transparent; then use a computerized coating machine to scrape the solution on the glass slide substrate and the polyimide substrate respectively. After coating, put it into a forced air drying oven and dry it at 65°C for 30min. After the solvent is completely volatilized, cure it for 30min under 365nm ultraviolet light and nitrogen atmosphere.

[0049] The UV-visible light transmittance of the transparent flexible wear-resistant coating with high hardness obtained in the above embodiment was tested by UV-1800 UV-visible spectrophotometer of Shimadzu Corporation of Japan, with a scanning range of 300-900 nm; the pencil hardness was tested by QHQ-A trolley pencil hardness tester of Shenzhen Sudre Company in accordance with the national standard GB 6739-86 "Coating Hardness Pencil Hardness Method"; the nanoindentation was tested by Hysitron TI 980 nanoindenter of Bruker Company of Germany, and then the nanoindentation hardness, modulus and elastic recovery rate were calculated by Oliver Pharr method; the surface morphology and roughness of the resin coating were tested by atomic force microscope of Dimension Icon model of Bruker Company of Germany; the wear test was tested by UMT-2 friction and wear tester of Bruker Company of Germany, and the coating morphology was photographed by Czech TESCAN MIRA LMS scanning electron microscope of Tescan Trading Co., Ltd. after wear.

[0050] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited thereto. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.

[0051] Table 1 shows the related properties of the transparent flexible wear-resistant coating with high hardness obtained in the above examples.

[0052]

Claims

1. A method for preparing a silsesquioxane resin coating, characterized in that: Ladder epoxy polysilsesquioxane and cage polysilsesquioxane are dissolved in an organic solvent, a photoinitiator is added, and the samples are dissolved by ultrasonication until they are clear and transparent; the samples are evenly coated on a substrate, and the substrate coated with the samples is then placed in a light-proof oven for drying to completely remove the solvent; The coating can be photocured by irradiation with ultraviolet light; The weight percentage of cage-type polysilsesquioxane in the polysilsesquioxane composition is 5-50%, and the amount of the photoinitiator is 0.1-10% of the total monomer weight.

2. The method according to claim 1, characterized in that The general chemical formula of the cage-type polysilsesquioxane is Si x O y R x , wherein x is 6, 7, 8, 10 or 12, y=1.5x, R is at least one of an epoxy group, an amino group, a carbonyl group, an ester group, a hydroxyl group, a mercapto group, a halogen atom, an ether group and an olefin, and the cage-type polysilsesquioxane is selected from at least one of the substances described in the following structural formula:

3. The method according to claim 1, characterized in that The general chemical formula of the ladder-shaped polysilsesquioxane is (SiRO 1.5 ) n , wherein R is at least one of an epoxy group, an amino group, a carbonyl group, an ester group, a hydroxyl group, a mercapto group, a halogen atom, an ether group and an olefin, and the ladder polysilsesquioxane structure is as follows:

4. The method according to claim 1, characterized in that: The photoinitiator is at least one of a free radical photoinitiator and a cationic photoinitiator.

Citation Information

Patent Citations

  • High-transparency flexible scratch-resistant coating, functionalized coating and preparation method of high-transparency flexible scratch-resistant coating

    CN114479665A

  • A POSS hybrid epoxy anticorrosive paint and coating thereof

    CN116200102B

  • Silsesquioxane having hot melt extrusion forming capability, highly transparent and highly heat-resistant plastic transparent substrate using same, and method of manufacturing same

    CN105873983A

  • Radiation curable coating composition, low-refractive-index layer, and antireflective film

    CN107406608A

  • Coating composition and film manufactured therefrom

    CN110139905A